Melatih Kemampuan Pemecahan Masalah Fisika melalui Penerapan Problem Based Learning Berbantuan Video pada Materi Fluida Statis di SMA Negeri 2 Mataram - Thufail Mujaddid Al-Qoyyim; Gunawan Gunawan; Wahyudi Wahyudi; Aris Doyan (Indonesian Journal of Education and Community Services, 2026)
This community service program aimed to train students’ physics problem-solving skills through the implementation of Problem Based Learning (PBL) supported by instructional videos on the topic of static fluids. The activity was conducted at SMA Negeri 2 Mataram involving eleventh-grade students. The program applied an implementative–participatory approach using a one-group pretest–posttest design. Students’ problem-solving skills were assessed based on four indicators adapted from Polya (1973): understanding the problem, planning a strategy, executing the strategy, and evaluating the solution. The results showed a significant improvement in all indicators after the implementation of PBL. The most substantial increase occurred in the indicators of planning and executing strategies, while the evaluation indicator, although improved, still requires further reinforcement. The integration of contextual videos at the problem orientation stage enhanced students’ conceptual understanding and engagement in the learning process. Overall, this community service activity effectively strengthened students’ systematic and reflective thinking skills in solving physics problems.